Autofluorescent proteins in single-molecule research: applications to live cell imaging microscopy. - Harms, G S (2001)
The spectral and photophysical characteristics of the autofluorescent proteins were analyzed and compared to flavinoids to test their applicability for single-molecule microscopy in live cells. We compare 1) the number of photons emitted by individual autofluorescent proteins in artificial and in vivo situations, 2) the saturation intensities of the various autofluorescent proteins, and 3) the maximal emitted photons from individual fluorophores in order to specify their use for repetitive imaging and dynamical analysis. It is found that under relevant conditions and for millisecond integration periods, the autofluorescent proteins have photon emission rates of approximately 3000 photons/ms (with the exception of DsRed), saturation intensities from 6 to 50 kW/cm2, and photobleaching yields from 10(-4) to 10(-5). Definition of a detection ratio led to the conclusion that the yellow-fluorescent protein mutant eYFP is superior compared to all the fluorescent proteins for single-molecule studies in vivo. This finding was subsequently used for demonstration of the applicability of eYFP in biophysical research. From tracking the lateral and rotational diffusion of eYFP in artificial material, and when bound to membranes of live cells, eYFP is found to dynamically track the entity to which it is anchored.